A new species of Sphaerephesia (Polychaeta: Sphaerodoridae) from Mamala Bay, south shore of Oahu, Hawaii - Magalhães, Wagner F.; Bailey–Brock, Julie H.; Barrett, Brendan M. (Zootaxa, 2011)
A new species of Sphaerephesia is described from Mamala Bay, south shore of Oahu, Hawaii. Sphaerephesia mamalaensis sp. nov., differs from its congeners by the absence of microtubercles and number and arrangement of body and parapodial papillae. This species is commonly found in low abundance in shallow (20 m) and deep–waters (500 m) adjacent to ocean outfall diffusers or dredge dump sites and has been resilient to the waste water treatment plume of the outfalls for the last 25 years. A comparative table with morphological characteristics of all seven recognized species of Sphaerephesia is provided.